Structural and Functional Alterations of Gut Microbiota in Males With Hyperuricemia and High Levels of Liver Enzymes - Sheng, Shifeng; Chen, Jingfeng; Zhang, Yuheng; Qin, Qian; Li, Weikang; Yan, Su; Wang, Youxiang; Li, Tiantian; Gao, Xinxin; Tang, Lin; Li, Ang; Ding, Suying (Frontiers in Medicine, 2021)
Objective: To investigate the correlation between the structure and function alterations of gut microbiota and biochemical indicators in males with hyperuricemia (HUA) and high levels of liver enzymes, in order to provide new evidences and therapeutic targets for the clinical diagnosis and treatment of HUA. Methods: A total of 69 patients with HUA (HUA group) and 118 healthy controls were enrolled in this study. Their age, height, waist circumference, weight, and pressure were measured. The clinical parameters such as fasting plasma glucose (FBG), aspartate aminotransferase (AST), alanine aminotransferase (ALT), serum uric acid (SUA), serum creatinine (Scr), total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), high-density lipoprotein (HDL), white blood cell (WBC), platelet (PLT), and absolute value of neutrophils (NEUT) were examined. We used whole-genome shotgun sequencing technology and HUMAnN2 MetaCyc pathway database to detect the composition and pathways of the gut microbiota. The main statistical methods were student's t test, chi-square tests, and Wilcoxon rank sum test. The correlations among bacterial diversity, microbial pathways, and biochemical indicators were evaluated by the R function “cor.test” with spearman method. Results: The gut bacterial diversity in HUA group reduced significantly and the community of the microbiota was of significant difference between the two groups. The pathways that can produce 5-aminoimidazole ribonucleotide (PWY-6122, PWY-6277, and PWY-6121), aromatic amino acids, and chorismate (COMPLETE-ARO-PWY, ARO-PWY, and PWY-6163) were enriched in the HUA group; while the pathways that can produce short-chain fatty acids (SCFAs, such as CENTFERM-PWY and PWY-6590) and the gut microbiotas that can produce SCFAs (Roseburia hominis, Odoribacter splanchnicus, Ruminococcus callidus, Lachnospiraceae bacterium 3_1_46FAA, Bacteroides uniformis, Butyricimonas synergistica) and equol (Adlercreutzia equolifaciens) were enriched in healthy controls. Conclusion: The structure and function of the gut microbiota in males with HUA and high levels of liver enzymes have altered apparently. In-depth study of related mechanisms may provide new ideas for the treatment of HUA.